Internal Control and Risk Mitigation in Regional Election Grant Fund Management: A Public Financial Governance Perspective - Weltri. H Daud; Wilson Bogar; Meidy S. S. Kantohe (JR Education, 2026)
This article analyzes the internal control system and risk mitigation practices used in the management of regional election grant funds at a provincial election supervisory institution in North Sulawesi. The study is positioned within public administration and public financial management because regional election grant funds are not ordinary operational funds; they are public resources transferred through a specific intergovernmental grant mechanism and used to support high-intensity electoral supervision. A qualitative descriptive approach was used through interviews, observation, and document analysis involving strategic, technical, and operational actors in grant fund management. The findings show that the management mechanism has been implemented through a relatively complete cycle of planning and budgeting, fund disbursement, activity implementation, administration and accountability, reconciliation, reporting, monitoring, and follow-up. Internal control supports accountability through authority division, layered verification, accountability checklists, hierarchical coordination, and follow-up on audit findings. However, the system remains less than optimal because recurring risks still appear, including delays in accountability reports, weak documentation, tax administration errors, travel cost discrepancies, limited human resources, and the absence of a specific risk register for regional election grant funds. The article argues that internal control is reasonably effective for detection, correction, and follow-up, but preventive control must be strengthened through standardized procedures, staff capacity development, digital archiving, risk-register preparation, and integration between planning, implementation, and accountability systems. The study contributes to public administration by linking internal control, risk mitigation, and electoral grant fund accountability in one analytical framework.